Abnormal cognitive function in treated congenital hypopituitarism. Issue 9 (20th August 2004) - Brown, K; Rodgers, J; Johnstone, H; Adams, W; Clarke, M; Gibson, M; Cheetham, T
Abstract : Aims: To assess cognitive function in school age children with congenital pituitary hormone deficiency (PHD). Methods: Ten children with PHD (aged 6.0–15.6 years, mean 11.5 years) and sibling controls (aged 8.7–14.9 years, mean 12.1 years) were assessed using the Wechsler Intelligence Scale for Children (WISC–III UK). Results: The patients' full scale IQ scores were all below average (mean 75, 95% CI 70–80), but were not significantly different to those of sibling controls (mean 82, 95% CI 75–89). There was no difference in verbal IQ between patients and siblings, but performance IQ was significantly reduced (mean 75, 95% CI 68–82 in patients; mean 88, 95% CI 80–96 in sibling controls). The reduced performance IQ reflected a poorer performance in tasks assessing perceptual organisational skills. Conclusions: Data suggest that children with PHD have an IQ that is below average when compared to the population norm and a reduced performance IQ when compared to sibling controls. This may reflect abnormal brain development or could be linked to the impact of hypoglycaemia or low thyroxine concentrations in early life. This information is of value when counselling parents and planning a child's care and education, although further, more extensive studies of patients and siblings are required.